2022
DOI: 10.1155/2022/6405085
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Hong Kong Students’ Esports Participation Intentions Using the Theory of Planned Behavior Approach: A Structural Equation Model

Abstract: Esports have grown to become a core part of popular culture in many countries, including Hong Kong. Albeit the low participation rates in Esports in Hong Kong, it was starting to gain traction, yet the local Esports advocates were experiencing challenges in promoting and popularizing the Esport. Hence, the current study was aimed to identify and reveal the determinants of participating in Esports, as well as strengthen the work on Esports behaviors using the theory of planned behavior (TPB), a reliable and val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 59 publications
1
17
0
Order By: Relevance
“…Prior studies have applied the TPB to understand an individual's decision-making processes in digital consumption, esports gameplay and video game live-streaming spectating (Chung et al, 2022;Koay et al, 2023;Leung et al, 2021;Srisathan and Naruetharadhol, 2022). Chung et al (2022) examined the modified TPB model to determine esports consumers' participating behavior among Hong Kong students. In their study, Chung et al (2022) found that esports participation and behavior toward esports entail playing esports games competitively.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Prior studies have applied the TPB to understand an individual's decision-making processes in digital consumption, esports gameplay and video game live-streaming spectating (Chung et al, 2022;Koay et al, 2023;Leung et al, 2021;Srisathan and Naruetharadhol, 2022). Chung et al (2022) examined the modified TPB model to determine esports consumers' participating behavior among Hong Kong students. In their study, Chung et al (2022) found that esports participation and behavior toward esports entail playing esports games competitively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Chung et al (2022) examined the modified TPB model to determine esports consumers' participating behavior among Hong Kong students. In their study, Chung et al (2022) found that esports participation and behavior toward esports entail playing esports games competitively. They found that ATT, SBN and PBC significantly impact behavioral intention.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though studies on acceptance analysis of online (mobile) games are easy to find, research in investigating esports based on established theories performed in previous studies is limited. For example, a recent study by P.-K. Chung et al (2022) investigated Hong Kong students' esports participation intentions using the theory of planned behavior (TPB). The results showed that all native TPB variables, such as attitude, subjective norm, and perceived behavioral control, significantly influence behavioral intention.…”
Section: Literature Reviewmentioning
confidence: 99%